2018
DOI: 10.1007/s00431-018-3179-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcome data of very low birth weight infants treated with less invasive surfactant administration in comparison to intubation and mechanical ventilation in the clinical setting of a cross-sectional observational multicenter study

Abstract: DRKS00004589 What is Known: • According to existing literature, LISA-treated infants seem to have some favors in terms of treatment and outcome data. Observational studies in routine clinical setting are missing. What is New: • Data of 407 VLBW infants collected in routine clinical setting showed that LISA-treated infants needed less mechanical ventilation and fewer days with supplemental oxygen and less analgesics and sedatives. A reduced risk of BPD could be showed. SGA infants seem to have higher risks of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Our study was able to define 36 days as a time of MV exposure that is associated with the development of moderate to severe BPD and, as a consequence, may have worse outcomes, such as greater severity of ROP and length of hospital stay. Therefore, it is suggested that MV should be avoided whenever possible, using strategies such as prophylactic CPAP and less invasive surfactant admnistration [26,27]. Moreover, MV should be interrupted as soon as possible, preferably before 36 days to reduce the risk of developing moderate to severe BPD, as well as to avoid impairments associated with the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was able to define 36 days as a time of MV exposure that is associated with the development of moderate to severe BPD and, as a consequence, may have worse outcomes, such as greater severity of ROP and length of hospital stay. Therefore, it is suggested that MV should be avoided whenever possible, using strategies such as prophylactic CPAP and less invasive surfactant admnistration [26,27]. Moreover, MV should be interrupted as soon as possible, preferably before 36 days to reduce the risk of developing moderate to severe BPD, as well as to avoid impairments associated with the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 15 studies, three used data from the German Neonatal Network, which reflects the actual clinical practice in more than 50 neonatal intensive care units across the country. 14,26,27 These studies used a matchedpair analysis in which each baby treated with the LISA technique was paired with a baby from a historic cohort, using similar significant characteristics, such as gestational age and Apgar scores. The studies presented in this review provide collective data from 4926 newborn infants who received surfactant by the LISA/SURE technique.…”
Section: Re Sultsmentioning
confidence: 99%
“…Most of the studies showed that LISA/SURE reduced the need for mechanical ventilation, ranging from 7.2% to 42% in treated infants. [14][15][16][17]22,[24][25][26][28][29][30][31][32]…”
Section: Main Outcomesmentioning
confidence: 99%
“…Unlike other reports where standard nasal CPAP was used with LISA [ 21 24 ], 63% of the procedures were carried out using BiPAP or NIPPV. While the potential advantages of BiPAP over CPAP remain uncertain, NIPPV proved to be more effective than nCPAP in reducing respiratory failure and the need for mechanical ventilation among preterm infants with RDS [ 7 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%